Z : a novel of Zelda Fitzgerald - Fowler, Therese (St. Martin's Press, 2013)
A tale inspired by the marriage of F. Scott and Zelda Fitzgerald follows their union in defiance of her father's opposition and her abandonment of the provincial finery of her upbringing in favor of a scandalous flapper identity that gains her entry into the literary party scenes of New York, Paris and the French Riviera.